Vasodilator and vasoconstriction inhibitor effect of Olea europaea (olive) leaf hydroalcoholic extract on rat aortic rings - Nexar-QH, Job (2013)
Objectives: To determine the vasodilator and anti-vasoconstrictor effect of Olea europaea (olive) leaf hydroalcoholic extract on rataortic rings and the mechanism involved. Design: Experimental. Location: Research and Scientific Development Center, Faculty ofMedicine, Universidad Nacional de San Agustin, Arequipa, Peru. Biological material: Leaves of Olea europaea and aortic rings ofRattus norvegicus, swiss albina variety. Interventions: Hydroalcoholic extract was obtained from Olea europaea leaves. Rat aortic ringswere placed in isolated organ chambers and the vasomotor activity was recorded with isometric tension transducer. Maximum basalcontraction occurred at CaCl2, and 6 mM vasodilator effect was determined at 25, 50, and 100 mg/mL doses of the hydroalcoholicextract. 1H-[1,2,4] oxadiazole [4,3-alquinoxalin-1-one] (ODQ) and nifedipine were used to determine the mechanism of action. Wecompared the inhibition of vasoconstriction after incubation for 30 minutes with the extract 100 mg/mL and with captopril 10 µM. Mainoutcome measures: Percentage of vasodilation and vasoconstriction. Results: There was vasodilatation of 7.20 ± 1.49%, 9.84 ± 1.42%,and 12.31 ± 1.16% for respectively 25, 50, and 100 mg/mL doses of hydroalcoholic extract; it was significant at doses of 100 mg/mL. Vasodilation increased after administration of ODQ 100 mM. Vasodilation was inhibited after incubation with ODQ 100 mM plusnifedipine 5 µM. No significant difference was found between vasoconstriction inhibition with captopril 10 µM or extract 100 mg/mL.Conclusions: Olea europaea leaves hydroalcoholic extract at 100 mg/mL dose had calcium channel blockade-vasodilator effect andvasoconstriction inhibitory effect on rat aortic rings.